Finite size scaling of hysteresis behavior: Monte carlo simulation on DIFFOUR model - Yongyut Laosiritaworn (2018)
In this work, Monte Carlo simulation was used to study the size dependence of the dynamic hysteresis properties of 2 dimensional ferroelectric system. The DIFFOUR model and Metropolis algorithm were used to investigate the size effect on hysteresis properties. From the simulation, it was found that the competition between the electric field parameters and the system size plays a crucial role on the phase-lag between the polarization and the electric field signals, which defines particular hysteresis properties. In describing the hysteresis behavior qualitatively, finite size scaling formalism, in a power law form, was used to predict relations among the field parameters, system size, and hysteresis. The purpose was to establish phenomenological knowledge of how dynamic perturbations affect the hysteresis in finite ferroelectric system. Comparison with related experiments was also discussed. Copyright © Taylor & Francis Group, LLC.